Motherhood, Career Aspirations, and Life Goals: Exploring Young Women’s Attitudes as a Factor in the Declining Fertility Rate in Sri Lanka - Michelle, Varuni; Bandara, Ruchira; Lakshman, Iresha (European Scientific Journal, ESJ, 2025)
The fertility rate in Sri Lanka has gradually declined over the last few decades. This study aims to explore how young Sri Lankan female undergraduates perceive motherhood in relation to their career aspirations and life goals. The study employed a mixed-method approach, following through a two-step process involving a survey and follow-up interviews, including in-depth interviews and focus group discussions. The sample included 300 female students from three faculties - Arts, Management, and Science, both first-year and final-year - at the University of Colombo. The study adopted a pseudo-longitudinal design, comparing differences in perceptions and attitudes toward motherhood between students. Findings indicate that the importance placed on motherhood varies by academic discipline, with arts and management students generally prioritising it more than science students. The study also revealed a shift in attitudes from first-year to final-year students, as exposure to academic life and career aspirations influenced the timing and conditions of motherhood. Career goals, financial stability, and lifestyle considerations emerged as key factors shaping decisions about motherhood, while balancing career and family remains a source of concern for many students. The findings highlight the interplay between societal expectations, personal values, and professional ambitions in shaping young women’s reproductive choices in Sri Lanka. In conclusion, undergraduates’ perceptions of motherhood are shaped by academic discipline and socio-economic factors, often leading to delayed motherhood due to anticipated role conflicts and financial considerations. Creating supportive policies, flexible work environments, and community-level interventions is essential to empower young women to balance career and family while making informed reproductive choices.